New records of recently described chemosymbiotic bivalves for mud volcanoes within the European waters (Gulf of Cádiz) - RUEDA, J.L.; URRA, J.; GOFAS, S.; LOPEZ-GONZALEZ, N.; FERNANDEZ-SALAS, L.M.; DIAZ-DEL-RIO, V. (Mediterranean Marine Science, 2012)
Chemosymbiotic bivalves are important members of cold seep communities and information on their distribution in the European waters is still quite scarce. This study reports the presence of living populations and shell remains of some recently described bivalves such as Lucinoma asapheus, Solemya elarraichensis and Acharax gadirae as well as Bathymodiolus sp. in the mud volcanoes of the Spanish Atlantic waters. Living populations of these species were thus far only found in Anastasya, Aveiro and Almazán mud volcanoes, together with other chemosymbiotic metazoa (Siboglinum spp.), suggesting the presence of moderate seepage activity. In other mud volcanoes (Albolote, Gazul), the benthic communities are dominated by sessile filter feeders on authigenic carbonates (chimneys, slabs) and only the shell remains of some chemosymbiotic bivalves were found, indicating earlier or very low seepage conditions. The present study elaborates on the known distribution of L. asapheus and S. elarraichensis to the European waters of the Gulf of Cádiz.